Vertikální talus: střednědobé výsledky operační terapie - Němejcová, E; Chládek, Petr; Rybka, Daniel; Schejbalová, Alena; Trč, Tomáš (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2015)
PURPOSE OF THE STUDY: The aim of the study was to clinically and radiographically evaluate the results of a two-stage surgical technique used in our department to treat congenital vertical talus. MATERIAL AND METHODS: In the years 1990-2010 we treated eight patients (nine feet). We used a two-stage surgical technique, with lengthening of the dorsiflexor muscles of the leg and the tibialis anterior muscle at the first stage. This was followed by cast fixation with the ankle in plantar flexion for 6 weeks. At the second stage, through a Cincinnati approach, the talonavicular and calcaneocuboid joints were reduced and the Achilles tendon and peroneal tendons were elongated. Two patients underwent the Grice extra-articular subtalar arthrodesis at the third stage. The post-operative outcomes were assessed based on radiographic findings of dorsoplantar views of the talocalcaneal angle (TC AP) and talar axis-first metatarsal base angle (TAMBA AP), lateral views of the weight-bearing talocalcaneal angle (TC LAT), talar axis-first metatarsal base angle (TAMBA LAT) and talotibial angle (TT). In all patients but one who was lost to follow-up, the radiographic and objective findings were evaluated with the 10-point scale described by Adelaar et al. RESULTS: The average follow-up was 8 years and 9 months. All radiographic findings showed improvement in all angles measured. The pre-operative values decreased in TC AP from 64.2° to 27.6°; in TC LAT from 48.8° to 30.4°; in TT from 158° to 109.3°; in TAMBA AP from 54.7° to 17.4°; in TAMBA LAT from 57.3° to 5.7°. The Adelaar scoring system was employed in seven patients of whom three had excellent, three good and one fair results. Two patients required additional surgery due to recurrence of the deformity DISCUSSION: Studies in recent years have shown a gradual diversion from extensive surgical procedures and a trend toward techniques like manipulation, serial casting application and minimal surgical intervention with talonavicular reduction and fixation. The Dobbs technique has so far shown good results but no long-term results have yet been available and therefore the number of recurrent cases is not known. CONCLUSIONS: The two-stage surgical technique used in our department proved to be very successful in a long-term follow-up, but the group of patients was too small to provide conclusive evidence. However, benefits of this technique are clearly apparent from the post-operative radiographic and objective findings assessed as very good.
Keywords: Foot Deformities, Congenital; Follow-Up Studies; Tenotomy; kosterní svaly; Muscle, Skeletal; Humans; sádrové obvazy; tenotomie; lidé; artrodéza; Achillova šlacha; Talus; Arthrodesis; talus; Achilles Tendon; vrozené deformity nohy (od hlezna dolů); následné studie; Casts, Surgical